POLARIZACIÓN EN EL MERCADO LABORAL Y AUSENCIA DE TRABAJO DECENTE PARA JÓVENES EN COLOMBIA - Calle Espinosa, Yhelin Cristina (2013)
This article aims to approach the phenomenon of polarization of labor income, taking into account thetype of contract and employment stability, in order to represent the working conditions that young peoplebetween 16 and 25 years face in Colombia. First we present a review of reports about current workingconditions, followed by an explanation of the concept of polarization; then we perform cluster analysis,which concludes that young people in the age range 16-25, are on average less paid per hour worked, andtheir situation is even more precarious if they do not have a written contract or if they have less than twelvemonths working in the same place.